Jejunal stromal tumor and neurofibromatosis - Kayser,Daniela Fonseca Lisboa (2019)
Abstract Gastrointestinal stromal tumors, although rare, are the most common primary mesenchymal neoplasms of the gastrointestinal tract and originate from the interstitial cells of Cajal. They present slow growth and symptoms such as bleeding, abdominal pain or discomfort, and the presence of an abdominal mass. The most affected organs are the stomach and small intestine. Differential diagnoses for gastrointestinal stromal tumor include adenocarcinoma and small intestine lymphoma, metastasis, and carcinoid tumor. Gastrointestinal stromal tumors have been associated with familial syndromes such as type 1 neurofibromatosis, considered a predisposing factor for tumors in the small intestine. This study aimed to report a case of gastrointestinal stromal tumor in the jejunal region in a patient with type 1 neurofibromatosis, followed-up for two years, who underwent laparoscopic segmental enterectomy and diagnosis determined by histopathology and immunohistochemistry. The diagnosis of small intestine gastrointestinal stromal tumor is challenging because of its low incidence, nonspecific symptoms, relative inaccessibility of the small intestine to conventional endoscopic examination, broad spectrum of radiological appearances, and the fact that the nature of the mass is difficult to determine with imaging examinations of the abdomen alone. Thus, the small intestine gastrointestinal stromal tumor may be erroneously diagnosed as pancreatic, gynecological, or mesenteric tumors. The literature does not present many reports on the association of jejunal gastrointestinal stromal tumor with neurofibromatosis. Understanding the tumoral behavior of small intestine gastrointestinal stromal tumor in this subgroup of patients would allow better follow-up.